2020
DOI: 10.3390/su12031146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Groundcovers on Reducing Soil Erosion and Non-Point Source Pollution in Citrus Orchards on Red Soil Under Frequent Heavy Rainfall

Abstract: Periods of consecutive days with heavy rain of high intensity are common in the red soil region of China, increasing unpredictable risks of soil erosion and non-point source pollution on sloping orchards. Grass cover, as a type of vegetation management, is useful for controlling soil erosion and pollution. However, the potential of different kinds of groundcover plants in combating soil erosion and non-point source pollution remains unclear under the rainfall conditions in this region of China. This study incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Other authors found tillage as the management with the highest soil losses and the alternative managements with the lowest ones [57]. Those results use to be relevant for groves, where the research need more surveys, for example, in the investigations conducted by Zhang et al, [35] in citrus plantation under heavy rainfall, as they found that in the comparison between Tillage and No-tillage resulted in a reduction in 26% in the runoff and 92% in the soil losses. Moreover, in vineyards was found a positive impact of the Tillage.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Other authors found tillage as the management with the highest soil losses and the alternative managements with the lowest ones [57]. Those results use to be relevant for groves, where the research need more surveys, for example, in the investigations conducted by Zhang et al, [35] in citrus plantation under heavy rainfall, as they found that in the comparison between Tillage and No-tillage resulted in a reduction in 26% in the runoff and 92% in the soil losses. Moreover, in vineyards was found a positive impact of the Tillage.…”
Section: Discussionmentioning
confidence: 74%
“…For instance, LĂłpez-Garrido et al, [25] tested reduced tillage, Khan et al, [26] used mulches, Gilley and Risse [27] used manure, Bazzoffi et al [28] urban compost, Faucette et al [29] mulch blankets, Mtambanengwu et al [30] weeds, Smets and Poesen [31] geotextiles, Chaowen et al [32] hedgerows, and Pan and Ma [33] grasses as a cover crop. Furthermore, it is widely accepted that soil erosion is a complex process that is difficult to understand and manage, but also it is accepted that there are already possible solutions [34], and those solutions can be applied in the agriculture [35] and forest lands [36]. For example, No-Tillage is an option to reduce soil erosion rates.…”
Section: Introductionmentioning
confidence: 99%
“…Area source water pollution occurs in a multifaceted manner and is involved in several dynamic processes, including rainfall runoff, soil erosion, pollutant accumulation, and leaching of soil solutes. Area source pollution is random, complex, uncertain, and characterized by hysteresis [ 3 , 4 , 5 ]. With rapid urbanization, the proportion of impervious surfaces in downtown areas has increased.…”
Section: Introductionmentioning
confidence: 99%
“…There is often a heavy rainfall precipitation and intensity here. As a result, RSHR is one of the most serious soil erosion areas in China [1][2][3][4]. Soil erosion has seriously affected the sustainable development of agriculture and economy in the entire region [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The amount of runoff and soil erosion depend on rainfall precipitation and intensity. At the same time, tillage methods and vegetation coverage type have an important impact [1,3]. Using the simulated rainfall methods, Wang et al studied the runoff and soil loss characteristics of 8 common land-use types under different rainfall conditions.…”
Section: Introductionmentioning
confidence: 99%